16.7k views
1 vote
HURRY PLEASE!

Which expression is equivalent to RootIndex 3 StartRoot 256 x Superscript 10 Baseline y Superscript 7 Baseline EndRoot?


a.4 x squared y (RootIndex 3 StartRoot x squared y cubed EndRoot)

b. 4 x cubed y squared (RootIndex 3 StartRoot 4 x y EndRoot)

c. 16 x cubed y squared (RootIndex 3 StartRoot x y EndRoot)

d. 16 x Superscript 5 Baseline y cubed (RootIndex 3 StartRoot y EndRoot)

2 Answers

5 votes

Answer:

hello :3 your answer is B

Explanation:

B for e2020

User Falke Design
by
5.2k points
5 votes

Answer:

Option b.


4x^3y^2\sqrt[3]{4xy}

Explanation:

we have the expression


\sqrt[3]{256x^(10)y^(7)}

Remember these properties


\sqrt[n]{x^m} =x^{(m)/(n)}


(x^(m))^(n) =x^(m*n)


(x^(m))(x^(n))=x^(m+n)

so


\sqrt[3]{256x^(10)y^(7)}=(256x^(10)y^(7))^{(1)/(3)}=(256^{(1)/(3)})(x^{(10)/(3)})(y^{(7)/(3)})

Rewrite the expression


256=(4^3)(2^2)


x^(10)=(x^9)(x)


y^7=(y^6)(y)

substitute


(256x^(10)y^(7))^{(1)/(3)}=((4^3)(2^2)(x^9)(x)(y^6)(y))^{(1)/(3)}

Applying properties of exponents


((4^3)(2^2)(x^9)(x)(y^6)(y))^{(1)/(3)}=(4^3)^{(1)/(3)}(2^2)^{(1)/(3)}(x^9)^{(1)/(3)}(x)^{(1)/(3)}(y^6)^{(1)/(3)}(y)^{(1)/(3)}

simplify


(4)^{(3)/(3)}(2)^{(2)/(3)}(x)^{(9)/(3)}(x)^{(1)/(3)}(y)^{(6)/(3)}(y)^{(1)/(3)}


(4)(2)^{(2)/(3)}(x)^(3)(x)^{(1)/(3)}(y)^(2)(y)^{(1)/(3)}


4x^3y^2\sqrt[3]{4xy}

User Petr Baudis
by
5.4k points